INFLUENCE DU TRAITEMENT THERMIQUE ET MECANIQUE SUR LES PROPRIETES MECANIQUES ET STRUCTURALES DES ACIERS AU MANGANESE MOULES. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Molded Steel with manganese have approximately 1,2% C and 12% Mn, this high proportion of manganese gives to this alloy a stable austenitic structure on a room temperature. The experimental methods used for metallurgical studies are spark optical emission spectroscopy, optical microscopy, scanning electron microscopy, micro-hardness and hardnesss test. Steel 1 is heat-treated constitued by 15,516 % of manganese, 2,677 % of chromuim and 1,286 % of carbon. Steel 2 is mechanically treated contains 13,454 % of manganese, 1,721 % of chromuim and 1,213 % of carbon . Steel 1 has sustained quench at 1070°C, for two differents maintaining times on oven 30 and 50 minutes for a thickness of 150 millimeters then for two differents thickness 100 and 150 millimeters for a time of 50 minutes. When maintaining time on the oven increase for low dimension, surface’s alloy become more ductile. We have applied a mechanical treatement manually on steel 2 surface, his hardness increase significantly.